Review of Infectious Medical Waste Management System at Haji Hospital Makassar - Era Pratiwi; Desiana Limbong; Andi Khairul Musyawir (International Journal of Public Health, 2025)
Environmental health such as proper medical waste management in accordance with existing requirements. The purpose of this study was to determine the sources of infectious medical waste at RSUD Haji Makassar. The research method used is a qualitative method with a post-positivistic or enterprising approach and observation. The types of data used are primary and secondary data. The results of the study indicate that at the sorting and reduction stage it has been implemented but in the sorting section there are still errors in plastic bags not being labeled regarding the type of waste, at the storage stage there are still errors in temporary storage places that can be accessed by animals, at the transportation stage there are still some that are not in accordance with the Regulation of the Minister of Environment and Forestry Number 56 of 2015 such as medical waste managers also do not use complete personal protective equipment and do not have a special route for waste transportation, at the processing stage it is not carried out because the incinerator in the hospital does not have an operational permit and at the stockpiling and burial stages it is also not carried out because medical waste management has been handed over to a third party. RSUD Haji Makassar pays more attention to all waste management processes that are not yet adequate and the management of incinerator use permits for better waste management.